Quantifying the external loads imposed by a commercially available set of swimming parachutes - Silveira, R. P.; Raineteau, Y.; Pla, R.; Bideau, B.; Nicolas, G.; Bideau, N. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION Swimming parachutes are widely used as a practical and low-cost tool for resisted swimming and its shape, cross-sectional area, as well as its speed, might influence the magnitude of the added load (Cortesi et al., 2019). Although its effects on stroke kinematics and coordination have been discussed in the literature, information on the training loads imposed by swimming parachutes are limited (Schnitzler et al., 2011) and usually not provided by the manufacturer. The aim of this study was to quantify the external loads imposed by a commercially available set of swimming parachutes, by establishing the hydrodynamic characteristics of parachutes of three different sizes.